Nilai-Nilai Bimbingan Konseling Pranikah dalam Buku Wonderful Journeys For a Marriage Karya Cahyadi Takariawan - Rida, Warda (JURNAL KONSELING GUSJIGANG, 2025)
This study aims to explore the Islamic pre-marital counseling values found in Wonderful Journeys For a Marriageby Cahyadi Takariawan. The article offers a new perspective by analyzing a literary work that has not been widely studied in the context of Islamic marriage preparation. Using a qualitative content analysis approach, the study identifies four core values: preparing for a sakinah (peaceful) family, building harmonious relationships, fulfilling family needs, and maintaining reproductive health. These themes align with the Decree of the Director General of Islamic Community Guidance No. 379 of 2017 on premarital counseling guidelines and provide a holistic framework for marriage readiness. The findings conclude that Takariawan's work offers comprehensive, spiritually grounded, and practical insights applicable for individual reflection and professional counseling, making a meaningful contribution to the development of Islamic pre-marital education.